- #1

- 6

- 0

Member warned about posting without the HW template

g(t)=½( f(t)+f(-t) ) h(t)=½( f(t)-f(-t) )

show its 2π periodic so: g(t+2π) = ½( f(t+2π)+f(t-2π) ) why does -t become t-2π ?

½( f(t)+f(-t) ) = g(t)

h(t+2π)=½( f(t+2π)-f(t-2π) )

½( f(t)-f(-t) ) = h(t) is this correct?

can anybody show me some similar examples please?

this is from a Fourier series question paper.

thanks

show its 2π periodic so: g(t+2π) = ½( f(t+2π)+f(t-2π) ) why does -t become t-2π ?

½( f(t)+f(-t) ) = g(t)

h(t+2π)=½( f(t+2π)-f(t-2π) )

½( f(t)-f(-t) ) = h(t) is this correct?

can anybody show me some similar examples please?

this is from a Fourier series question paper.

thanks